In silico design of novel pyridazine derivatives as balanced multifunctional agents against Alzheimer’s disease - Mourad Aloui; Mohamed El fadili; Somdutt Mujwar; Mohammed Er-rajy; Hatem A. Abuelizz; Sara Er-rahmani; Sara Zarougui; Elhalaoui Menana (Scientific Reports)
Abstract Alzheimer’s disease (AD) necessitates innovative therapeutic approaches that target its multifaceted pathology. This study investigates a series of 2-aminoalkyl-6-(2-hydroxyphenyl)pyridazin-3(2H)-one derivatives as potential multi-target ligands for AD, aiming to simultaneously inhibit acetylcholinesterase (AChE) and amyloid-beta (Aβ) aggregation. To assess the therapeutic potential of these compounds, we employed a comprehensive computational approach, incorporating 2D-QSAR modeling, molecular dynamics simulations, molecular docking, and ADMET property analysis. Based on these analyses, we designed 13 novel pyridazine derivatives exhibiting favorable interactions with key AD-related proteins, enhanced dynamic stability within protein binding sites, and adherence to established drug-likeness principles. Notably, these compounds demonstrated promising oral absorption (96%) and exhibited no significant toxicity in preliminary assessments. These results indicate that the novel pyridazine derivatives warrant further investigation as promising multifunctional agents for the treatment of Alzheimer’s disease.